PENGEMBANGAN TEKNIK PENILAIAN CATEGORIZING GRID UNTUK MELATIHKAN KECAKAPAN MENGANALIS PADA MATAKULIAH VOCABULARY I - Siti Azizah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
Analysis skill is advance cognitive skill that the students must have in their learning, including in Vocabulary I. It studies how the assessment forms of categorizing grid technique which can practice students’ skill in analyzing. After researched, tested definite sample, revised based on expert’s suggestion, as well as the implementation, there is a finding that the technique of assessment is valid and good technique. Assessment technique develop to support learning activity in Vocabulary I in “compound nouns” topic using categorizing grid to train students’ skill in analyzing is acceptable. The proofs are: the assessment running well, there are solutions for the obstacles during the assessment activity, students’ activity running well, students give positive response.